Compulsory Teaching of the Holy Quran: Bridging Tradition & Innovation for Holistic Islamic Educational Progress - Tehmina Rafiq (Al-Amīr Research Journal for Islamic Studies, 2025)
The nexus of technology innovation and the Teachings of the Holy Qur’an offers a promising pathway for societal progress, particularly in the context of education. Islamic teachings, rooted in principles such as accountability, ethical conduct, and the pursuit of knowledge, provide a robust framework for shaping technological advancement within the Islamic studies discipline. Modern technology, including artificial Intelligence (AI) and IT solutions, can significantly enhance the understanding and teaching of Islamic education by facilitating access to knowledge, fostering interactive learning, and bridging traditional teaching barriers and innovative technology. Examples of successful integration, such as the digital Quran platform and Islamic educational apps, demonstrate how traditional values can be harmonized with cutting-edge tools to enrich teaching practices. However, this integration presents challenges. Ethical concerns, such as privacy invasion, misuse of AI, and the Potential dilution of Islamic tradition, underscore the need for a vigilant approach in developing balanced strategies that merge tradition with innovation, addressing issues like the digital divide and cultural resistance. Collaborative efforts to align STEM advancements with Islamic ethical standards are essential for ensuring that technological contributions support holistic societal development without compromising Islamic teachings. Islamic teachings on morality and social responsibility can serve as guideline principles for creating ethical frameworks that integrate advanced technologies into education and societal practices. Ultimately, bridging the gap between tradition and innovation requires a collaborative and adaptable approach, ensuring that technological progress aligns with the enduring values of Islamic thought and contributes meaningfully to societal improvement. This study highlights the role of Islamic values in shaping the responsible integration of technology and fostering societal progress through balanced innovation. Keywords: Islamic Thought, Technological Innovation, Educational Development, Artificial Intelligence (AI), Traditional and Innovative Methods